2012
DOI: 10.2478/v10181-011-0144-2
|View full text |Cite
|
Sign up to set email alerts
|

Application of real-time PCR for detection of Lawsonia intracellularis and Brachyspira hyodysenteriae in fecal samples from pigs

Abstract: The aim of the study was to develop and validate real-time PCR method for the quantification of Lawsonia intracellularis and Brachyspira hyodysenteriae in porcine feces. Before the optimization process was performed two different extraction methods were compared to select the more efficient one. Based on the results achieved at this stage the boiling procedure was rejected and a commercially available silica-membrane based method was chosen for further analysis. The primers and the Taqman probe for B. hyodysen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…In terms of fecal samples, 7/162 (4.32%) were positive by qPCR, from 4/20 (20%) of the evaluated farms (Table 2). Zmudzki et al (2012) investigated the efficiency of qPCR, using the same primer as the present study, and found good sensitivity and specificity values in the detection of L. intracellularis in swine feces, demonstrating the possibility of using the technique in the diagnosis of proliferative enteropathy. These animals, which were positive in molecular biology, originated from four out of the seven (4/7) farms with positive serology, indicating the circulation of the agent on them.…”
Section: Resultsmentioning
confidence: 53%
“…In terms of fecal samples, 7/162 (4.32%) were positive by qPCR, from 4/20 (20%) of the evaluated farms (Table 2). Zmudzki et al (2012) investigated the efficiency of qPCR, using the same primer as the present study, and found good sensitivity and specificity values in the detection of L. intracellularis in swine feces, demonstrating the possibility of using the technique in the diagnosis of proliferative enteropathy. These animals, which were positive in molecular biology, originated from four out of the seven (4/7) farms with positive serology, indicating the circulation of the agent on them.…”
Section: Resultsmentioning
confidence: 53%
“…Pooled fecal samples were homogenized in single-use plastic containers and total genomic DNA was extracted using a commercial isolation kit (Genomic Mini, A&A Biotechnology, Gdynia, Poland), according to the manufacturer's recommenda- Real-time PCR amplification of total DNA extracted from fecal samples for detection of L. intracellularis and B. hyodysenteriae was carried out according to the method described previously (Zmudzki et al 2012).…”
Section: Pcr Techniquesmentioning
confidence: 99%
“…Next, slides were analysed by in situ hybridization (ISH) for PCV2 identification ( 16 ) and were haematoxylin and eosin stained for histopathological examination. The faeces and scrapings were subjected to a real-time PCR for identification of Lawsonia intracellularis and Brachyspira hyodysenteriae ( 25 ). Additionally, parasitological analyses of faeces and intestinal content collected from the colon were performed with the use of flotation in a saturated NaCl solution supplemented with sugar with specific gravity of 1.3 ( 22 ) and with decantation ( 24 ).…”
Section: Methodsmentioning
confidence: 99%